Carcass traits of Muzaffarnagari lambs under intensive and semi-intensive management systems - PAL, U K; AGNIHOTRI, M K; SINHA, N K (The Indian Journal of Animal Sciences, 2013)
Muzaffarnagari lambs (n=23) were slaughtered at 6.5 months of age to study the meat production traits under intensive and semi-intensive systems of management. Live animal and carcass measurements differed significantly (P< 0.05) between the groups. Lambs maintained under intensive system had higher (P